2008
DOI: 10.1007/s00468-008-0274-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of leaf attributes and water use efficiency in Quercus suber along a rainfall gradient

Abstract: The aim of our study was to assess the intraspecific variation of a range of leaf attributes and carbon isotope discrimination (D), in Quercus suber, along an 800 mm rainfall gradient in Portugal. We measured specific leaf area (SLA), leaf thickness (LT) and density, and used leaf carbon isotope content as an integrated record of water use efficiency. The values of SLA of Q. suber were strongly, positively correlated with rainfall, decreasing as rainfall decreased. This reduction was mainly driven by LT, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 43 publications
5
22
0
Order By: Relevance
“…This result agrees with Damesin et al (1997), who observed lower δ 13 C leaf in Q. ilex and Q. pubescens on the wettest sites (1,134 mm) than on the driest sites (663 mm). In terms of carbon isotope discrimination (Δ leaf ), similar results have been reported by Goveiras and Freitas (2008). Both authors found a significant positive correlation between Δ leaf and the rainfall gradient (491-1,299 mm) of the Q. suber distribution in Portugal, and linked this result to an adjustment of gas exchange at leaf level according to water availability.…”
Section: Water Status Of Seedlingssupporting
confidence: 85%
“…This result agrees with Damesin et al (1997), who observed lower δ 13 C leaf in Q. ilex and Q. pubescens on the wettest sites (1,134 mm) than on the driest sites (663 mm). In terms of carbon isotope discrimination (Δ leaf ), similar results have been reported by Goveiras and Freitas (2008). Both authors found a significant positive correlation between Δ leaf and the rainfall gradient (491-1,299 mm) of the Q. suber distribution in Portugal, and linked this result to an adjustment of gas exchange at leaf level according to water availability.…”
Section: Water Status Of Seedlingssupporting
confidence: 85%
“…This supports our statement of a well-watered site based on the observed plasticity of this functional trait according to drought [61,62]. From this first observation, we then conclude that the carbon assimilated by trees is preferentially allocated to the aboveground biomass (leaf and stems), and the measured stem biomass is actually in the highest range of referenced forest sites in the Mediterranean basin [57,63,64], with impressive twig elongations (up to 28.5 cm) compared to [65] where apical twig elongations usually vary between 3.3 cm and 19.6 cm.…”
Section: Bellif Ecosystem Peculiar Fertile Conditions Within the Medisupporting
confidence: 76%
“…With the expansion of the leaves, however, their shape became thin. It has been previously reported that SLA is positively correlated with precipitation (Gouveia and Freitas, 2009). Additionally, we found that leaf N was influenced by precipitation.…”
Section: Relationship Between Leaf N and Sla And Nuementioning
confidence: 94%